Clinicians' perceptions of rationales for rehabilitative exercise in a critical care setting: A cross-sectional study. Issue 2 (March 2017) - Nickels, Marc; Aitken, Leanne M.; Walsham, James; Watson, Lisa; McPhail, Steven
Abstract: Background: Rehabilitative exercise for critically ill patients may have many benefits; however, it is unknown what intensive care unit (ICU) clinicians perceive to be important rationale for the implementation of rehabilitative exercise in critical care settings. Objective: To identify which rationales for rehabilitative exercise interventions were perceived by ICU clinicians to be important and determine whether perceptions were consistent across nursing, medical and physiotherapy clinicians. Methods: A cross-sectional study was undertaken among clinicians (nursing, medical, physiotherapy) working in a mixed medical surgical ICU in an Australian metropolitan tertiary hospital. Participants completed a customised web-based questionnaire developed by a clinician working-group. The questionnaire consisted of 11 plausible rationales for commencing rehabilitative exercise in ICUs based on prior literature and their own clinical experiences grouped into 4 over-arching categories (musculoskeletal, respiratory, psychological and facilitation of discharge). Participants rated their perceived importance for each potential rationale on a 5-point Likert scale. Results: Participants ( n = 76) with a median (interquartile range) 4.8 (1.5, 15.5) years of experience working in ICUs completed the questionnaire. Responses were consistent across professional disciplines. Clinicians rated rehabilitative exercise as either 'very much' or 'somewhat' important for facilitating discharge ( n = 76, 100%), reducing muscle atrophy ( n = 76, 100%), increasing muscle strength ( n = 76, 100%), prevention of contractures ( n = 73, 96%), reducing the incidence of ICU acquired weakness ( n = 62, 82%), increasing oxygenation ( n = 71, 93%), facilitating weaning ( n = 72, 97%), reducing anxiety ( n = 60, 80%), reducing depression ( n = 64, 84%), reducing delirium ( n = 53, 70%), and increasing mental alertness ( n = 65, 87%). Conclusions: Any shortcoming in implementation of rehabilitation exercise is unlikely attributable to a lack of perceived importance by nursing, medical or physiotherapy clinicians who are the most likely clinicians to influence rehabilitation practices in ICUs. It is noteworthy that this study examined self-reported perceptions, not physiological or scientific legitimacy of rationales, or clinician behaviours in practice.